Synthesis of Non-Cubic Nitride Phases of Va-Group Metals (V, Nb, and Ta) from Metal Powders in Stream of NH3 Gas under Concentrated Solar Radiation - Shohoji, Nobumitsu (2022)
ABSTRACT: Using a high-flux solar furnace, loosely compacted powders of Va-group transition metal (V, Nb, and Ta) were reacted with stream of NH3 gas (uncracked NH3 gas) being heated by concentrated solar beam to a temperature (T) range between 600 and 1000 degrees C. From V, sub-nitride V2N (gamma phase) and hypo-stoichiometric mono-nitride VN possessing fcc (face-centered cubic) crystal lattice structure (delta phase) were synthesized. On the other hand, in the reaction product from Nb and Ta, hexagonal mono-nitride phase with N/M atom ratio close to 1 (epsilon phase) was detected. The reaction duration was normalized to be 60 min. In a conventional industrial or laboratory electric furnace, the synthesis of mono-nitride phase with high degree of crystallinity that yield sharp XRD peaks for Va-group metal might take a quite long duration even at T exceeding 1000 degrees C. In contrast, mono-nitride phase MN of Va-group metal was synthesized for a relatively short duration of 60 min at T lower than 1000 degrees C being co-existed with lower nitride phases.